The influence of Atmosphere store, technology and halal certification on culinary café business income / Suginam Suginam … [et al.] - Suginam, Suginam; Anggraini, Dwi Pertiwi; Ningsih, Trans; Siahaan, Riki Rikardo; Utomo, Dito Putro; Deli Sianturi, Ronda; Rahayu, Sri (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
This study aims to determine the effect of store atmosphere, technology and halal certification on culinary business income. This research method is a quantitative method, the setting in this study is to measure culinary business income in Medan. The objects in this study were cafes in the city of Medan, while the research subjects were entrepreneurs/owners of culinary cafes in the city of Medan. The number of samples in this study were 100 respondents who were selected using purposive sampling method with non-probability sampling technique, with the analytical tool is multiple linear regression. The results of the analysis of this study are that store atmosphere has a significant effect on culinary business income, technology has an effect on culinary business income and the application of halal certification has a significant effect on culinary business income in the city of Medan.